Attenuated inflammatory profile following single and repeated handgrip exercise and remote ischemic preconditioning in patients with cerebral small vessel disease - Landman, Thijs R. J.; Uthman, Laween; Hofmans, Inge A. H.; Schoon, Yvonne; de Leeuw, Frank-Erik; Thijssen, Dick H. J. (Frontiers in Physiology, 2022)
Background. Similar to remote ischemic preconditioning bouts of exercise may possess immediate protective effects against ischemia-reperfusion injury. However, underlying mechanisms are largely unknown. This study compared the impact of single and repeated handgrip exercise versus remote ischemic preconditioning on inflammatory biomarkers in patients with cerebral small vessel disease (cSVD). Methods. In this crossover study, 14 patients with cSVD were included. All participants performed 4-days of handgrip exercise (4x5-minutes at 30% of maximal handgrip strength) and remote ischemic preconditioning (rIPC; 4x5-minutes cuff occlusion around the upper arm) twice daily. Patients were randomized to start with either handgrip exercise or rIPC and the two interventions were separated by >9 days. Venous blood was drawn before and after one intervention, and after 4-days of repeated exposure. We performed a targeted proteomics on inflammation markers in all blood samples. Results. Targeted proteomics revealed significant changes in 9 out of 92 inflammatory proteins, with four proteins demonstrating comparable time-dependent effects between handgrip and rIPC. After adjustment for multiple testing we found significant decreases in FMS-related tyrosine kinase-3 ligand (Flt3L;16.2% reduction; adjusted P-value: 0.029) and fibroblast growth factor-21 (FGF-21; 32.8% reduction adjusted P-value: 0.029) after single exposure. This effect did not differ between handgrip and rIPC. The decline in Flt3L after repeated handgrip and rIPC remained significant (adjusted P-value=0.029), with no difference between rIPC and handgrip (adjusted P-value=0.98). Conclusion. Single handgrip exercise and rIPC immediately attenuated plasma Flt3L and FGF-21, with the reduction of Flt3L remaining present after 4-days of repeated intervention, in people with cSVD. This suggests that single and repeated handgrip exercise and rIPC decrease comparable inflammatory biomarkers, which suggests activation of shared (anti-)inflammatory pathways following both stimuli. Additional studies will be needed to exclude the possibility that this activation is merely a time effect.